Case studies in the traditional food sector : a volume in the Consumer Science and Strategic Marketing series - Cavicchi, Alessio; Santini, Cristina (Woodhead Publishing in food science, technology, and nutrition., 2018)
Consumer Science and Strategic Marketing: Case Studies in the Traditional Food Sector aims to close the gap between academic researchers and industry professionals through real world scenarios and field-based research. The book explores how consumer and sensory science has been implemented in the food industry for achieving the following strategic aims: rejuvenating product image, shaping new market places, achieving market differentiation and geographical diffusion, achieving customer loyalty, promoting traditional features of the product and defining product positioning in competitive environment. There is an emerging demand from food industry professionals and undergraduate and postgraduate students who attend business and agricultural studies courses who want to gain practical information through real cases and field-based research. This book aims to answer the following questions, amongst others: How research in the field of consumer science became relevant for marketing strategies?, Which tangible economic and financial outcomes have been obtained by the joint work of sensory scientists, researchers in marketing field and food business professionals?, and which communication methods and practices have been relevant to make the most of R & D in the food industry? Through case studies, successful examples and practices are provided, with newer inputs for further theoretical investigation given. Both current and future professionals in the food industry will gain insights that can be used in their business environment.